Slab Detachment, Mantle Flow, and Crustal Collision in Eastern Sicily (Southern Italy): Implications on Mount Etna Volcanism. Issue 9 (24th August 2020) - Barreca, G.; Branca, S.; Corsaro, R. A.; Scarfì, L.; Cannavò, F.; Aloisi, M.; Monaco, C.; Faccenna, C.
Abstract: New data and interpretations of the geodynamics of eastern Sicily point to deep crustal shortening taking place in the area. Reconstructions of the lithospheric system, seismicity distribution, and stress state in the crust indicate that deformation is expressed by a large thrust‐ramp cutting through the entire lower plate. The tectonic structure is propagating directly beneath the Mount Etna volcano, one of the few active volcanoes in Europe. Geostructural interpretation of tomographic sections allows for interpretations of the compressional structure as originating in response to trench‐parallel breakoff of the Ionian slab. Following the simple assumption that if a slab retreats, it must either be compensated or alternatively pushed by the fore‐arc mantle, we argue that the opening of a gateway in the slab has encouraged the fore‐arc mantle to flow toward the Mount Etna region. Mantle mobilization has had a twofold influence on both magmatic source mixing and the inception of underplating processes beneath the Mount Etna. A shortening prevailing over extension in the crust below the volcano seems to have a significant impact on the dynamics of the Mount Etna volcanic system, which manifested through anomalous signals over the last thousands of years. Since a tectonic inversion of previous dilatational magma pathways is expected in such a converging setting, the documented variations are believed to be consistent with a volcano experiencing a declining phase. Comparison with other extinct volcanic systems in the southern Tyrrhenian margin, lying atop a detached slab and involved in contraction, provides insights into the evolution of Mount Etna. Key Points: The crust below the volcano is currently involved in deep‐seated contraction as result of subduction cessation and collision onset Increasing in explosiveness, lateral eruptions and changes in lava composition are interpreted as controlled by deep‐seated crustal shortening beneath the volcano According to the reconstructed geodynamics, anomalies in the late evolution of Mount Etna could indicate a declining stage for the volcano